The Palgrave Handbook of Public Administration and Management in Europe
LIII, 1302 p. 35 illus.
Keywords: This Handbook offers a systematic review of state-of-the-art knowledge on public administration in Europe. Covering the theoretical, epistemological and practical aspects of the field, it focuses on how public administration operates and is studied in European countries. In sixty-three chapters, written by leading scholars, this Handbook considers the uniqueness of the European situation through an interdisciplinary and comparative lens, focusing on the administrative diversity which results from the multiplicity of countries, languages, schools of thought and streams of investigation across Europe. It addresses issues such as multi-level administration and governance, intensive cross country cooperation in administrative reform policy, and public accountability under different systems. It also considers the issue of welfare service delivery, at a time of major economic and societal challenges, as well as understudied emerging issues like Islamic Public Administration and the dynamics of public sector negotiations. With contributions from key experts in Public Administration and Public Management, this cutting edge Handbook offers a significant contribution to the field of comparative public administration, policy and management.